Fiscal rules in good times and bad - Christoph Paetz (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2020)
I estimate fiscal reaction functions to analyze the cyclical behavior of discretionary measures in the euro area and the potential impact of changes in the fiscal framework. The core is to analyze whether fiscal rules have an asymmetric impact on discretionary measures over the cycle. First, results confirm the general perception that overall discretionary fiscal policy in the EMU is marginally procyclical. Procyclicality is, however, characterized by strong fiscal tightening in contractions while reactions in upturns are neutral. Second, fiscal rules marginally increase countercyclical policy responses in upturns, but strongly reinforce destabilizing procyclical polices in downturns. Interestingly, expenditure rules perform comparably better with regard to the stabilization objective than budget or debt rules.
Keywords: E6; H11; H6; 330; Fiscal rules; fiscal reaction function; fiscal cyclicality; debt sustainability; EMU